Descrição semântico-pragmática da escalaridade e aditividade de até, mesmo e ainda em português brasileiro - Rosa, Pamela Soares (2022)
The literature presents a vast study on the scalar additive lexical item even in the English language, on which issues related to its two implications, additive and scalar, are discussed (Karttunen and Peters, 1979; Fauconnier, 1975; Lycan 1991; Barker, 1991; Francescotti, 1995), conditions for the good use of the lexeme (Bennett, 1982; Kay, 1990; Lycan, 1991; Berckmans, 1993; Francescotti, 1995), syntactic-semantic relations (Karttunen and Peters, 1979; Roth, 1985; Wilkinson, 1996; Rullmann, 1997), even scalarity (Greenberg, 2015/2017), in addition to the issues of the independence between implicatures (Crnič, 2011; Wagner, 2015). Inspired by this broad discussion, studies on this lexeme have also been carried out in other languages, such as Greek (Giannakidou, 2007) and Spanish (Schwenter, 2002; Chamorro, 2008; Lahiri, 2008; Herburguer, 2013). In view of this research context and aware of the incipient study on this lexeme in Brazilian Portuguese (BP), we propose the development, in this thesis, of a semantic-pragmatic description of lexemes até, mesmo and ainda, which present these same properties, scalarity and additivity. Thus, the general objectives of the dissertation are to elucidate which operation the lexemes até, mesmo and ainda perform in relation to the phrase on which they have scope in BP and what is the nature of this operation (conventional or conversational). The semantic-pragmatic description of the scalarity of these lexemes is developed in order to clarify other issues related to these problems, such as meaning and scope, scalarity and additivity, licensed implicatures and context influence. A review of the literature on even is initially presented, ranging from basic, more intuitive studies on the lexeme, to more recent studies involving semantic formalization and studies on EVEN in Greek and Spanish; studies are also presented on the grammaticalization of até, mesmo and ainda with emphasis on the possible meanings of each lexeme. Two proposals are developed on these lexemes, involving scope and meaning, and scalarity and additivity. Based on the proposals, we conclude that the lexemes até and mesmo may present additivity, however, necessarily, they present scalarity, while the lexeme ainda may present scalarity and always indicates additivity. Based on this, we argue that the implicatures conveyed by até and mesmo are (i) conventional implicature of scalarity and (ii) conversational implicature of additivity; while the lexeme ainda, in its turn, presents (i) conventional implicature of additivity and (ii) conversational implicature of scalarity.